Atypical pityriasis rosea mimicking annular lichen planus. - Serarslan, G.; Atik, E.; Sarıkaya, G. (European Journal of Pediatric Dermatology, 2010)
Pityriasis rosea is a common papulosquamous disease seen in children and adults. Although diagnosis of classic pityriasis rosea is usuallly made by history and clinical exam alone, in atypical cases diagnosing may be problematic. The disease may display atypical clinical features such as in morphology, size, distribution, number, and site of the lesions. We present a 7-year-old boy diagnosed as pityriasis rosea with atypical morphology and distribution. There were annular lichen planus like lesions and less commonly papular lesions about 0.5-3 cm in size on the face, forearms and dorsal part of his hands. To our knowledge this type of morphology had not been reported to date.